Association between maternal and paternal employment and their children's weight status and unhealthy behaviours: does it matter who the working parent is? - Néboa Zozaya; Juan Oliva-Moreno; Laura Vallejo-Torres (BMC, 2022)
Abstract Background The growing number of employed women has been associated with an increase in the prevalence of overweight and obesity in children. We sought to determine whether childhood overweight/obesity in Spain is associated with labour participation of mothers and fathers, and whether the identity of the main caregiver has an influence on child's weight and unhealthy behaviour. Methods We used microdata from the 2010 and 2014 Health Behaviour in School-Aged Children surveys performed in Spain (n = 32,694). Logistic and linear multi-level regression models were applied to assess the association between parental employment and children's self-reported weight status, accounting for school effects and controlling for socioeconomic factors. Separated binary models were also fitted for consumption of fruit, sweets, screen viewing and sedentarism. Results In most cases, the significant associations between children's weight and their parents' work status disappeared once the models were adjusted for family wealth and education. However, we found persistent associations for some groups. Girls under 13 years-old living in households where the mother was the only employed parent were more likely to be affected by obesity and to report a higher body mass index value. Children in this type of household were more likely to show unhealthy lifestyles related to diet and leisure time activities. Conclusions Parents' socioeconomic characteristics had a protective effect on their children's risk of obesity. Unhealthy behaviours were observed in households with a non-working father and a working mother, although the link with obesity was limited to girls. Our results suggest the need for a more equally shared burden of caregiving.